Polisemie al microscopio - Rovere, Giovanni (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2022)
In interlingual comparison, cases of apparent polysemy, existing only from the perspective of the other language, are well known. Sometimes, however, the search for contextually appropriate equivalents brings to light distinctive semantic features overlooked in the lexicographic description of the source lexical unit.